Evolução da participação das startups da construção civil e mercado imobiliário no Brasil - Goulart, Gustavo Engler (Universidade Federal de São Carlos, 2025)
This study aims to map the evolution of startup participation in the construction and real estate sectors over time, analyzing their relationship with macroeconomic data and the impacts generated in the industry. To achieve this, concepts such as Industry 4.0 and Construction 4.0 were explored, as they have driven the adoption of advanced technologies in construction and real estate properties. Additionally, the main technologies used by construtechs and proptechs—including Building Information Modeling (BIM), drones, 3D printing, augmented reality, and artificial intelligence—were analyzed to understand how these innovations are transforming the way the construction sector operates and interacts with its clients.The results identified 1,071 startups in the construction and real estate sectors, reflecting a growth of 523% in the number of companies from 2014 to 2024. Of these, 298 were classified as construtechs and 773 as proptechs, with growth rates of 562% and 508% over the same period, respectively.It was observed that construtechs have concentrated on the digitization and automation of construction processes, enhancing efficiency and minimizing waste. Meanwhile, proptechs have contributed to the modernization of the real estate market by offering solutions that optimize user experience and asset management. Although this study reveals a significant rise in the number of startups in Brazil in recent years, civil engineering remains a relatively underexplored field in academic research, especially regarding innovation and technology-driven entrepreneurship. This gap highlights both challenges and opportunities for developing innovative solutions that can modernize the sector. Therefore, this research contributes to a deeper understanding of startup dynamics in construction and reinforces the need for further academic investigation on the subject.
The evolution of construction and real estate startups' involvement in the brazilian market
Keywords: Inovação; Indústria 4.0; Startups; Construtechs; Proptechs; Innovation; Industry 4.0; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL